Rwanda smallholder agriculture commercialization survey: Overview using selected categorical variables - Warner, James; Rosenbach, Gracie; Benimana, Gilberthe Uwera; Mugabo, Serge; Niyonsingiza, Josue; Mukangabo, Emerence; Dushimayezu, Bertrand; Nshimiyimana, Octave; Ingabire, Chantal; Spielman, David J. (International Food Policy Research Institute, 2023)
This report provides a comprehensive statistical overview of agricultural household data collected by IFPRI from a smallholder commercialization survey in late 2022. Sampled to be representative to the provincial level, ten households were surveyed in 202 villages for a total of 2,020 households interviewed. The survey covers a wide range of topics including household demographics, agricultural farm holdings, input use, crop choice, levels of commercialization and other non-farm sources of income. The statistical tables are generally presented by principal categorical variables of interest which include provinces, gender and age of household head (youth/mature), as well as size of land holdings. These designations are meant to provide general insights into the current state of agricultural households in Rwanda. Building on this report, future research, on more specific topics of interest, will be performed to build a more comprehensive understanding of agricultural household economic behavior for broader understanding as well as potential policy engagement.